Electrocardiographic changes among beta-thalassemic major patients in ibn al-baladi thalassemia center-Baghdad - Mohammed, Suhad Jassim; Al-Lami, FarisH.; Hussein, Mousa Qasim (AL-Kindy College Medical Journal, 2013)
Background :Thalassemia is an autosomal disease of the haemoglobin. Two types of thalassemia are recognized: thalassemia major and thalassemia intermedia. The most serious cardiac complication in thalassemia major is due to multiple blood transfusions rather than the disease itself, which is due to iron overload. Cardiomyopathy is the most common cardiac defect that occurs with iron overload. Pricarditis, congestive heart failure and arrhythmias are due to hemosidrosis and chronic aneamia. Aim of the study: to demonstrate the prevalence and types of electrocardiographic changes among thalassemic patients with aged over ten years old.